The development and location of industries in greater Cape Town, 1652-1972 - Whittingdale, John (Department of Environmental and Geographical Science, 2016)
Many geographical stud±es have been made of the whole or parts of the City of Cape Town. These include a short general study of the structure and functions of the city from 1652 to 1958 by William J. Talbot Cape Town as a World City (in Zum Problem der Weltstadt), several sociological studies by P. Scott and a delimitation of the C.B.D. boundary of the city by D.Davies and 'The Growth and Development of Cape Town' by Margaret Marshall. Others include studies of individual industrial suburbs. It does not appear that a complete study of the industrial structure of the city has ever been attempted. In this thesis an attempt has therefore been made to trace, as far as possible, the growth and development of industry in Greater Cape Town from the time of the first settlement in 1652.